2017
DOI: 10.1093/neuros/nyx485
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surgical Start Time on Complications Associated With Neurological Surgeries

Abstract: Patients with SSTs between 21:01 and 07:00 are at an increased risk of developing morbidity compared to patients with an SST earlier in the day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
1
15
2
Order By: Relevance
“…Such studies have found no relationship between afterhours surgery and complications for pediatric appendectomy 6 or adult neurosurgery. 7 Few data are available concerning surgical outcomes and complications related to the time of day for scheduled elective surgical procedures. One study identified an elevated risk of morbidity for nonemergent procedures starting between 4 p.m. and 6 p.m. and a further elevated risk for morbidity in cases starting after 6 p.m. 8 Although generally considered a rather safe procedure, outpatient pediatric tonsillectomy carries with it a 14-day readmission rate of approximately 7.6% with revisits attributable to postoperative hemorrhage, acute pain and fever/vomiting/ dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have found no relationship between afterhours surgery and complications for pediatric appendectomy 6 or adult neurosurgery. 7 Few data are available concerning surgical outcomes and complications related to the time of day for scheduled elective surgical procedures. One study identified an elevated risk of morbidity for nonemergent procedures starting between 4 p.m. and 6 p.m. and a further elevated risk for morbidity in cases starting after 6 p.m. 8 Although generally considered a rather safe procedure, outpatient pediatric tonsillectomy carries with it a 14-day readmission rate of approximately 7.6% with revisits attributable to postoperative hemorrhage, acute pain and fever/vomiting/ dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Other specialties have studied the effect of surgical start time on postoperative morbidity and mortality and have demonstrated a later start time as an independent risk factor for poor outcomes. 5,6,19 Yet, this finding is not consistent across all specialties and institutions with some studies finding no difference. 2022…”
Section: Discussionmentioning
confidence: 72%
“…morning chronotypes in the evening) which has potential implications for surgical success and complications. 4 Linzey et al 5 reported an increased risk of morbidity following neurosurgery when the case started between 21:01 and 07:00, while Kork et al 6 demonstrated an increased risk of postoperative mortality in all surgical cases starting between 13:00 and 17:00 compared to 08:00 to 11:00. It is more difficult to show a difference in ocular surgery as most cases are elective and scheduled during regular hours.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported an increased incidence of surgical com- plications following operations with a late SST. 15 These differences could reflect surgeon fatigue, the more chaotic nature of a night encounter, or the desire for heroic operations that may have been declined during the day. It could also represent the fact that, at our institution, the neurosurgical resident serves as the primary person offering surgery during "off hours," whereas the entire team, including neurosurgical attending personnel, is available for discussion with the family during "on-hour" presentations.…”
Section: Discussionmentioning
confidence: 99%